The lichens of forest rocky communities of mountain Olovgora (Arkhangelsk Region, Northwest Russia) - Tarasova, Viktoria; Sonina, Angella; Androsova, Vera; Stepanchikova, Irina (Folia Cryptogamica Estonica, 2015)
The present study reports 223 species and three subspecies of lichens from forest rocky communities of mountain Olovgora, which is the highest point of the Vetreny Poyas ridge (Arkhangelsk Region, NW Russia). A total of 82 species are new for the mainland area of Arkhangelsk Region. The species Bryoria glabra has been reported for the first time for European Russia. Two recorded lichen species, Cladonia bellidiflora and Lobaria pulmonaria, are in the Red Data Book of Arkhangelsk Region. The occurrence of old-growth forests, high heterogeneity of conditions, presence of an altitudinal gradient and the proximity to the sea lead to the rich diversity of lichens in this area.